THE TRANSFORMATION OF CHILDHOOD IN A MODERN SOCIETY AND ITS EDUCATIONAL CONTEXT - Biernat, Tomasz (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The main aim of this article is to discuss two ways of perception of childhood in a modern society. The first way, which is preferred by essentialists, refers to the biological background of childhood and its traditional meanings. The second way of understanding childhood treats childhood as a kind of social construct. Both definitions bring up various consequences in the institutional education, raising children in families as well as in socialization of the young generation and sharing responsibility for education.